EFFECTIVENESS OF PROBLEM BASED LEARNING AS A STRATEGY TO FOSTER PROBLEM SOLVING AND CRITICAL REASONING SKILLS AMONG MEDICAL STUDENTS - Asad, Munazza; Iqbal, Khadija; Sabir, Mohammad (Journal of Ayub Medical College Abbottabad, 2015)
Background: Problem based learning (PBL) is an instructional approach that utilizes problems or cases as a context for students to acquire problem solving skills. It promotes communication skills, active learning, and critical thinking skills. It encourages peer teaching and active participation in a group. Methods: It was a cross-sectional study conducted at Al Nafees Medical College, Isra University, Islamabad, in one month duration. This study was conducted on 193 students of both 1st and 2nd year MBBS. Each PBL consists of three sessions, spaced by 2-3 days. In the first session students were provided a PBL case developed by both basic and clinical science faculty. In Session 2 (group discussion), they share, integrate their knowledge with the group and Wrap up (third session), was concluded at the end. A questionnaire based survey was conducted to find out overall effectiveness of PBL sessions. Results: Teaching through PBLs greatly improved the problem solving and critical reasoning skills with 60% students of first year and 71% of 2nd year agreeing that the acquisition of knowledge and its application in solving multiple choice questions (MCQs) was greatly improved by these sessions. They observed that their self-directed learning, intrinsic motivation and skills to relate basic concepts with clinical reasoning which involves higher order thinking have greatly enhanced. Students found PBLs as an effective strategy to promote teamwork and critical thinking skills. Conclusion: PBL is an effective method to improve critical thinking and problem solving skills among medical students.